Perceptions and feelings about physical changes in climacteric women - Julia Costa Curta; Anne Marie Weissheimer (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To know the perceptions and feelings about the physical changes of climacteric women in a city of Rio Grande do Sul. Methods: Qualitative exploratory descriptive study developed with 16 women on public spaces of Porto Alegre/RS/Brazil, in September and October of 2018; data gathered through semi-structured interviews and submitted to thematic analysis. Results: Four themes were found: "Knowledge (or not) on climacteric and menopause (and their differences)", "Changes perceived", "Changes felt", and "How to deal with climacteric and menopause". Conclusions: Women have little information on climacteric; it is the nurses' responsibility to clarify about these phases, offer emotional support and indicate physical activities that may ease their signs and symptoms.